KONSEP KETUHANAN DALAM GEGURITAN SATYANING SAWITRI - I Komang Dedi Diana; Ida Ayu Dwidyaniti Wira (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Bali is famous for its high-quality cultural arts, including one of its spiritual nuances. One of the literary works that contains the value of vocal art is Geguritan Satyaning Sawitri. This Geguritan was composed by I Made Suputra, Called Geguritan Satyaning Sawitri because it featured the character of Dewi Sawitri who was very loyal to her husband and was very respectful of his father-in-law King Jamat Sena who had been displaced due to losing the war, so that his country was dominated by the enemy. Geguritan Satyaning Sawitri takes the background of the story in the Mahabrata book, which is about the story of king Agung Aswapati having a daughter named Dewi Sawitri. After a husband who is famous for being honest and very loyal to her husband (pati brata satyeng Laki). Geguritan Satyaning Sawitri consists of 50 pada, using 4 types of pupuh, namely: Sinom 8 pada, Ginada 20 pada, Adri 5 pada, and Ginanti 17 pada. The concept of God in Geguritan Satyaning Sawitri emphasizes sraddha and devotion to God in its manifestation as Sanghyang Titah, Sanghyang yama.